Analisis Kontrastif dalam Pembelajaran Pelafalan Bunyi Segmental Bahasa Inggris (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Palangka Raya, 2020)
Contrastive analysis is aimed to identify aspects of the differences ordissimilarities between two or more languages being contrasted. There aretwo kinds of approach in contrastive analysis, applied contrastive analysisand pure contrastive analysis. Applied contrastive analysis is aimed to solvepedagogical problems, while the pure one is aimed to study languagetypology. Applied contrastive analysis is discussed in this article. There aretwo procedures to contrast the components of contrasted languages, theyare (1) description and (2) comparison. Based on the results, Englishvowels which are difficult to pronounce by Indonesian students are (1) longvowel sounds (tense vowels) [i:, u:, ?:, ?:, ?:]and (2) short vowels sounds(lax vowels) [æ]. Contrastive analysis is included into structural linguisticswhich has many significances, namely (1) to overcome the difficulties in learning a foreign language; (2) to predict the students’ difficulties inlearning a foreign language, and (3) the foreign language teachers canutilize the results of contrastive analysis to arrange learning materials.